Stability evaluation of interdigitated liposomes prepared with a combination of 1,2-distearoyl-sn-glycero-3-phosphocholine and 1,2-dilauroyl-sn-glycero-3-phosphocholine - Adrar, Nabil; BAHADORİ, FATEMEH; BAHADORİ, FATEMEH; Ceylan, Fatma Duygu; TOPÇU, GÜLAÇTI; TOPÇU, GÜLAÇTI; Bedjou, Fatiha; Çapanoğlu Güven, Esra (My University, 2021)
BACKGROUND In order to obtain small and homogenous liposomes encapsulating gallic acid (GA) with interdigitated leaflets, a combination of phosphatidylcholine (PC) of medium length sn-1 and sn-2 acyl chains with PC of longer acyl chains at both sn1 and sn2 positions were employed. Four formulations respectively consisting of 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC); DSPC/1,2-dilauroyl-sn-glycero-3-phosphocholine (DSPC/DLPC) (1:1, mol mol(-1)); DSPC/DLPC (3:1, mol mol(-1)) and Lipoid S75, were prepared. For each formulation, the stability of liposomes during storage was investigated.